2018
DOI: 10.1177/1403494818809856
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ experiences during the first postnatal week at home after early discharge of mother and baby from the maternity unit: A meta-synthesis

Abstract: Aim: The aim of this study was to explore and describe fathers’ experiences during the first postnatal week after early discharge of mother and baby from the maternity unit. Methods: A meta-synthesis. Inclusion criteria: peer-reviewed qualitative single studies of fathers’ experiences during the first week after early discharge (defined as less than 72 hours postpartum) from hospital after the birth of a healthy singleton baby born between weeks 37 and 40. Databases: Cumulative Index to Nursing and Allied Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…From a supply-side perspective, our findings highlight the importance of home visits, particularly in HIC settings, as an opportunity for fathers and family members to become more involved in PNC and to have their own queries and concerns addressed. These findings resonate with evidence from other studies, which suggest that fathers feel more comfortable discussing their concerns with health professionals in their own homes and are better able to develop a father–infant bond under these circumstances 41 42. The recently published WHO recommendations on maternal and newborn care for a positive postnatal experience support this view and recommend home visits during the postnatal period across all care settings 3…”
Section: Discussionsupporting
confidence: 80%
“…From a supply-side perspective, our findings highlight the importance of home visits, particularly in HIC settings, as an opportunity for fathers and family members to become more involved in PNC and to have their own queries and concerns addressed. These findings resonate with evidence from other studies, which suggest that fathers feel more comfortable discussing their concerns with health professionals in their own homes and are better able to develop a father–infant bond under these circumstances 41 42. The recently published WHO recommendations on maternal and newborn care for a positive postnatal experience support this view and recommend home visits during the postnatal period across all care settings 3…”
Section: Discussionsupporting
confidence: 80%
“…In our study, we also found that the mothers and the fathers had different concerns about their new role as a parent. While the mothers were more concerned about breastfeeding and establishing a relation to the child, it was more important for the fathers to get confirmation that the baby was developing and acting “normal.” Similar findings about fathers' concerns and their need to have confirmed that everything is alright with the baby was described in a meta-synthesis by Brunstad et al ( 34 ), who also reported that having emotional support from professionals empowered their feelings of confidence in the transition to fatherhood. This reinforces the potential importance of having different professionals involved in the home visit to give both parents enough space to discuss their concerns and support them in parenthood.…”
Section: Discussionsupporting
confidence: 77%
“…For many parents, taking their baby home is a time of trepidation and excitement and having staff validate these feelings is important to leaving the hospital feeling empowered and capable. A meta-synthesis by Brunstad et al [ 21 ] reported that, for fathers, the influence of midwife interaction and communication was crucial to building confidence prior to being discharged from hospital. For mothers, the midwives’ ability to empower women is also critical as it influences the mother’s general wellbeing and comfort, particularly during the first weeks following birth.…”
Section: Discussionmentioning
confidence: 99%